2015
DOI: 10.3109/15569527.2015.1034360
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical everolimus and sunitinib on corneal neovascularization

Abstract: Topical administration of both everolimus and sunitinib reduced VEGFR-2 levels and inhibited CNV. In additon, everolimus reduced ERK 1/2 levels and seems to be more effective than sunitinib on CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Other experiments showed that topical application of both sunitinib and everolimus could decrease VEGFR2 levels and suppress CNV. Further, everolimus could decrease ERK 1/2 levels, which appeared to be more useful than sunitinib on the treatment of CNV …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 97%
“…Other experiments showed that topical application of both sunitinib and everolimus could decrease VEGFR2 levels and suppress CNV. Further, everolimus could decrease ERK 1/2 levels, which appeared to be more useful than sunitinib on the treatment of CNV …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 97%
“…Its design was based on sunitinib. Preclinical studies have indicated that sunitinib can inhibit corneal neovascularization [ 31 ]. Vatalanib, pazopanib, and sorafenib are tyrosine kinase inhibitors similar to sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…143 Both agents have recently been shown to effectively reduce VEGFR-2 levels and inhibit CoNV in a rat model. 144…”
Section: Vegf Pathwaymentioning
confidence: 99%